Falsehood in Speech and Some Means of Its Expression - Mnatsakanyan, Lusine (Armenian Folia Anglistika, 2012)
The current article investigates the psychological-linguistic characteristic of falsehood in speech.  Different types of falsehood are introduced, and their application in specific speech situations are discussed.  Linguistic as well as extralinguistic means of falsehood in speech have been examined to reveal the role of movements/gestures in falsehood identification.